Keuse van 'n vooruitskattingstegniek - S. C. Gous (South African Journal of Business Management, 1984)
– Choice of a forecasting technique Business forecasting has developed rapidly over the past few years as a result of the increasing complexity of the environment of the firm. Some researchers assert that businesses apparently experience three problems with reference to forecasting: a preference for the application of certain techniques is built up so that more suitable techniques are not utilized; not all relevant factors are taken into consideration in the choice of the most suitable technique; and managers often do forecasting themselves even though they possess little knowledge thereof. To handle the increasing variety and complexity of managerial forecasting problems, many forecasting techniques have been developed in recent years. Each has its special use, and care must be taken to select the correct technique for a particular application. The manager as well as the forecaster has a role to play in technique selection and the better the manager understands the range of forecasting possibilities, the more likely it is that a company's forecasting efforts will bear fruit.
Keywords: 650